أثر زواج الحاضنة بغير قريب محرم بين الشريعة الإسلامية والقانون الجزائري - غربي هالة; قديري سهيلة (University of Eloued جامعة الوادي, 2024)
قمنا في هذه الدراسة ببيان الأثر المترتب على زواج الحاضنة بأجنبي عن الصغير المحضون، حيث تنعكس هذه الآثار على حضانتها له بين كل من الشريعة الإسلامية والقانون الوضعي الجزائري، وتوصلنا من خلال هذا البحث أن مسألة زواج الحاضنة بغير قريب محرم من مسقطات الحضانة والتي بها تمنع الحا"In this study, we have explained the effects of the custodian’s marriage to someone who is not relative of the child in custody, and how it reflects on her custody, according to both Islamic law and Algerian positive law. We concluded through this research that the issue of the custodian’s marriage without someone other than a relative mahram can cause loss of the custody. However, both the positive law, as well as Islamic law, consider in this particular issue taking into account the interest of the child, and so sometimes despite the imbalance of conditions the custody can still be maintained .
Keywords: الحضانة، زواج، سقوط، زواج، حاضنة، محضون، أثر، مصلحة.; Nursery; Marriage; Fall; Babysitter; Cuddles; Impact; Interest